Uncle Sam in pinstripes evaluating U.S. federal credit programs - Elliott, Douglas J. 1959- (Brookings Institution Press, 2011)
"Explains the pervasiveness and complexity of the many federal lending programs, their effect on the overall economy, the costs, as well as the benefits and risks they pose, and actions that should be taken to ensure such programs are more efficient and effective"--Provided by publisher.